2013
DOI: 10.3389/fphys.2013.00067
|View full text |Cite
|
Sign up to set email alerts
|

Trace conditioning in insects—keep the trace!

Abstract: Trace conditioning is a form of associative learning that can be induced by presenting a conditioned stimulus (CS) and an unconditioned stimulus (US) following each other, but separated by a temporal gap. This gap distinguishes trace conditioning from classical delay conditioning, where the CS and US overlap. To bridge the temporal gap between both stimuli and to form an association between CS and US in trace conditioning, the brain must keep a neural representation of the CS after its termination—a stimulus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 108 publications
(196 reference statements)
1
22
1
1
Order By: Relevance
“…In olfactory trace conditioning, the reinforcer arrives after the odor stimulus has already terminated, and there is no overlap between the two stimuli. In this situation, the reinforcer arrives when the cytosolic Ca 2+ in KC axon terminals is already back to baseline ( Galili et al, 2011 ; Shuai et al, 2011 ; Szyszka et al, 2011 ; Dylla et al, 2013 , 2017 ). Where, then, is coincidence detection possible for associative trace conditioning?…”
Section: Introductionmentioning
confidence: 99%
“…In olfactory trace conditioning, the reinforcer arrives after the odor stimulus has already terminated, and there is no overlap between the two stimuli. In this situation, the reinforcer arrives when the cytosolic Ca 2+ in KC axon terminals is already back to baseline ( Galili et al, 2011 ; Shuai et al, 2011 ; Szyszka et al, 2011 ; Dylla et al, 2013 , 2017 ). Where, then, is coincidence detection possible for associative trace conditioning?…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that KC adaptation currents retain a representation of stimulus identity, resembling a prolonged odor trace (Perisse and Waddell, 2011;Dylla et al, 2013). In our model, an odor trace present in adaptation levels extends well beyond the brief spiking responses.…”
Section: Odor Representation In Adaptation Currentsmentioning
confidence: 76%
“…Yet, it is still not known whether the same individual mushroom body intrinsic neurons serve both modalities or if there are dedicated subsets for each modality. Moreover, mushroom body neurons were suggested to maintain odor traces in olfactory conditioning [ 8 , 35 ]. Thus, it would be interesting to test whether this is also the case in visual conditioning.…”
Section: Discussionmentioning
confidence: 99%